2002
DOI: 10.1177/1073191102009003003
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Criminal Attitudes and Associates (MCAA)

Abstract: Recent meta-analysis has demonstrated that attitudes and associates are among the best predictors of antisocial behavior. Despite this finding, there are few psychometrically developed and validated measures of criminal and antisocial attitudes and associates. This study reviews the theoretical and empirical development of the Measures of Criminal Attitudes and Associates (MCAA), which is composed of two parts. Part A is a quantified self-report measure of criminal friends. Part B contains four attitude scales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
151
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 165 publications
(153 citation statements)
references
References 53 publications
1
151
0
1
Order By: Relevance
“…Item selection was based on the item's factor loading as reported by Mills and Kroner (2001) as well as on its applicability to our sample. Cronbach alphas were 0.89 for Violence (items 1, 13, 37 and 41, original item numbers from Mills & Kroner, 2001) Reduction of public self-awareness was measured by four items: 'When I am with fellow fans, I feel strong and I am much more reckless', 'During the match I never think of the fact that someone could punish me for shouting abuse to the other side's fans', 'In a group I don't feel personally responsible for shouting angry remarks' and 'Together with the fans of my side I shout bad things about others, because they can't catch me anyway' (a ¼ 0.67, M ¼ 2.93, SD ¼ 1.06). Two items measured social identity: 'I am proud of our side' 1 and 'I resemble the other members of our side' (a ¼ 0.72, M ¼ 3.29, SD ¼ 1.36).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Item selection was based on the item's factor loading as reported by Mills and Kroner (2001) as well as on its applicability to our sample. Cronbach alphas were 0.89 for Violence (items 1, 13, 37 and 41, original item numbers from Mills & Kroner, 2001) Reduction of public self-awareness was measured by four items: 'When I am with fellow fans, I feel strong and I am much more reckless', 'During the match I never think of the fact that someone could punish me for shouting abuse to the other side's fans', 'In a group I don't feel personally responsible for shouting angry remarks' and 'Together with the fans of my side I shout bad things about others, because they can't catch me anyway' (a ¼ 0.67, M ¼ 2.93, SD ¼ 1.06). Two items measured social identity: 'I am proud of our side' 1 and 'I resemble the other members of our side' (a ¼ 0.72, M ¼ 3.29, SD ¼ 1.36).…”
Section: Methodsmentioning
confidence: 99%
“…Mills, Kroner, and Hemmati (2004) revealed that delinquent and criminal behaviour is often accompanied by negative attitudes toward legal institutions and authorities and positive attitudes toward delinquent peers (Gendreau et al, 1979), and pride in delinquent acts (Shields & Whitehall, 1994). Moreover, Mills and Kroner (2001;Mills, Kroner, & Forth, 2002) have developed an inventory for assessing these pro-criminal attitudes known as the Measures of Criminal Attitudes and Associates (MCAA). The theoretical framework of the MCAA is based on Ajzen's (1991) theory of planned behaviour.…”
Section: Attitudesmentioning
confidence: 99%
See 3 more Smart Citations